Ecotheological Exegesis: a Study of Indonesian Women’s Ulema Congress Opinion - Moh. Rofqil Bazikh (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2024)
Environmental damage is a problem which gets attention even religionist regards about it. The interpretation of Koran verses presents to elaborate the ethical principle for nature and environment. One of the groups which attempts to interpret ecological verses within Koran is Indonesian Women’s Ulema Congress (KUPI). This congress held firstly in 2017 and then 2022. In first congress, KUPI discussed three crucial issues from sexual abuse, child marriage until damage of nature. This research aims to analyze KUPI interpretation regarding environmental demage. The type of research is qualitative based on library research (kajian pustaka). The data are gathered from literatures which are relevant with the topic. Primary source is earned from Result and Process Document of Indonesian Women’s Ulema Congress (KUPI) I in 2017. Secondary sources are earned from literature, journal, article, book, which relate with topic of environment and ecotheology. This research uses analytical descriptive which analyzes the content such as in primary source. To analyze the finding of research uses ecotheology concept initiated by Seyyed Hossein Nasr and Mary Evelyn Tucker. There are phases in this research from collecting, identifying, analyzing and concluding the data based on the theoretical framework. The conclucion that KUPI interpretation on Koran verse is ecotheological such as Nasr and Tucker perception. There are nineteen verses which are elaborated to support contrary position toward environmental demage. Some of KUPI interpretations are more progressive than interpretation in classical exegesis.